1996
DOI: 10.2105/ajph.86.2.240
|View full text |Cite
|
Sign up to set email alerts
|

Preconceptional and prenatal multivitamin-mineral supplement use in the 1988 National Maternal and Infant Health Survey.

Abstract: This paper examines the prevalence of multivitamin-mineral supplement use before and during pregnancy, as well as predictors of nonuse, in 9953 women who delivered live infants in the 1988 National Maternal and Infant Health Survey. Ninety-seven percent of the women were advised to take multivitamin-mineral supplements in prenatal care. Sixty-seven percent of Black mothers took supplements during pregnancy, as compared with 84% of White mothers. Multivariate analysis revealed that Black mothers; mothers who ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 13 publications
1
27
1
Order By: Relevance
“…In the 1988 National Maternal and Infant Health Survey of a nationally representative sample of U.S. women who delivered a child in that year, 83% of respondents reported that they took supplements with multiple vitamins and minerals ≥3 days/week for 3 months after they found out they were pregnant (64 ). Significantly smaller percentages of black women; Eskimo, Aleut, or American Indian women; women aged <20 years; and women having less than a high school education reported taking these supplements.…”
Section: Vol 47 / No Rr-3 Mmwrmentioning
confidence: 99%
“…In the 1988 National Maternal and Infant Health Survey of a nationally representative sample of U.S. women who delivered a child in that year, 83% of respondents reported that they took supplements with multiple vitamins and minerals ≥3 days/week for 3 months after they found out they were pregnant (64 ). Significantly smaller percentages of black women; Eskimo, Aleut, or American Indian women; women aged <20 years; and women having less than a high school education reported taking these supplements.…”
Section: Vol 47 / No Rr-3 Mmwrmentioning
confidence: 99%
“…11,12,15,16,[20][21][22] Women who had fertility treatments were much more likely to take FA supplements around the time of conception than women who did not have any treatments. Women who had a previous live birth, especially women with 2 or more live births, had an increased risk of no intake.…”
Section: Commentmentioning
confidence: 99%
“…4,[11][12][13][14] Intake during early pregnancy is critical because most birth defects occur during the first few weeks of pregnancy. For example, neural tube closure is completed by day 28 after conception, or 6 weeks after the last menstrual period.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The National Maternal and Infant Health Survey from 1988 reported that, of the 97% of mothers who had been advised to consume a prenatal vitamin supplement, 83% reported adherence to recommendations during pregnancy. 54 In 2000, a survey based on the Pregnancy Risk Assessment Monitoring System further found that up to 41% of women in 19 states consumed a multivitamin supplement more than 4 times per week. 55 More recently, data from NHANES 1999-2006 showed an average of 74% of pregnant women consume a multivitamin or multimineral supplement containing folic acid.…”
Section: Vitamin Intake During Pregnancymentioning
confidence: 99%